(untitled) (Journal on studies and research of academic knowledge, 2013)
Aloe is a perennial plant of the Liliaceae family, which can reach up to thirteen feet high, belongs to the group of plants xerophytes, presents a short stem and large leaves, fleshy, thick, straight and rounded at the back, are between 30 and 60 cm long by 7-8 cm wide, arranged in a basal rosettes. There are about 360 species of aloe that live in tropical and even hybridize in many gardens. The culture is done in loose, sandy to sandy loam and calcareous, with very good drainage. The most cultivated species is the A. barbadensis. . The aim of this study was to determine the antimicrobial effect in vitro of Aloe vera (L) Burm and Aloe arborescens on Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Candida albicans performing prospective descriptive cross-sectional study with an analytical component by the method of Kirby Bauer in 20 samples belonging to 10 species the A. vera and 10 the species A. arborescens. Used the leaf mesophyll (gel) and 70%, 50 % ethanolic solutions, and aqueous 50% against a minimum battery strains inocula at different concentrations corresponding to 0.5, 1 and 2 Scale Mac Farland to evaluate the antimicrobial activity. When performing diffusion technique with aqueous solutions and gel both species has not been evidenced inhibition bacterial or fungal development in the 20 samples tested, but using the solutions gel/ ethanol at 50% and 70%, there was considerable evidence inhibitory power in 10 samples corresponding to Aloe vera gel recording no inhibition when using arborescens Aloe gel, so it is recommended to use Aloe vera gel in ethanol solution for treating external injuries affecting the epidermis.